Xylanase Activity and Kinetics Comparison During Pulping of Gossypium arboreum and Gossypium barbadense - Shahid, Gulshan; Jabbar, Abdul; Zahid Qureshi, Muhammad; Ikram Aujla, Muhammad; Suleman, Muhammad; Sohail, Muhammad (Asian Journal of Chemistry, 2011)
In this paper, xylanase enzyme was employed for pulping of two cotton species Gossypium arboreum and Gossypium barbadense. Initially ground cotton was used to investigate the enzymatic hydrolytic effect. Xylanase activity was optimized at various substrate concentrations, different pH, temperature and for the presence of various metal ions. Xylanase gave best activity with 1 g substrate, pH 8 at 50 ºC. Xylanase activity for Gossypium arboreum was 1.132 μmol/ min/mL at pH 5 and 20 ºC. Xylanase activity for Gossypium barbadense was determined at pH 6-9. Km was found to be 722 mol and Vmax was 109 μmol/min. Xylanase shows good potential to replace the toxic chemicals of paper and pulp industry.